Analysis of the physical and chemical aspects of frozen pulp of native fruit from the cerrado (Research, Society and Development, 2023)
The objective of this study was to measure and evaluate pH values of frozen fruit pulps from cerrado region of Brazil, such as açaí, bacuri, cupuaçu, caju, cajá, graviola, murici and tamarindo, through a quantitative experimental research, evaluated with selected water samples.Therefore, it becomes interesting to investigate the fruits from cerrado, to know if they can have potential for the development of erosive lesions in the oral cavity. This research was performed at the ITPAC laboratory, located in the state of Tocantins, specifically in the capital city of Palmas. The pH measurements were performed by previously calibrated pH-meter equipment. All samples evaluated reported acid pH values, consistent with data established by the MinL9gotiposistry of Agriculture, Livestock and Supply of Brazil. As result in this study all samples of fruits pulps reported high acid pH values.The consumption of fruit pulps with high acidity promotes the dental erosion, process that is injurious to oral health.